ASPEK PEMIMPIN HEBAT MENURUT 2 TIMOTIUS 2:1-25 DITINJAU DARI ASPEK GRAMATIKAL DI GEREJA MASEHI ADVENT HARI KETUJUH INDONESIA - Ferdinand Butarbutar (Jurnal Theologia Forum STFT Surya Nusantara, 2018)
The contents of this writing would be focussed more deeper to discuss and to explore message of 2 Timothy 2:1-25 from grammatical aspect and historical events of how apostle Paul sent letter to Timothy. Furthermore, analyzing the word, interpretate the meaning of the language,or dialects, which is an important order to Timothy as a young servant whom is going to carry its task to continue ministrerial mission and to fulfilled his heart as a strong leader near in the future. Then, Timotthy’s leadership style could be as an agood example to the member of the Seventh-Day Adventist Organization in Indonesia. Leader is a person who can guide, lead and supervise others to pursue a certain level of organization’s goal and to control its subordinates, Shelton Ken (2002:6). No one can doubt and blame the attending of a first missionary Pastor Ralp Waldo Munson whom had been arrive December year of 1889 in Padang (West Sumatra). This visitation became a pillar of the Sevent-Day Adventist movement in Indonesia. This research will describe more specifically from grammatical perspectives and historical views. The factors that are gong to elaborates are endure harship; hard working; patient; faithful; heartely; frankly speaking; empty word; self-control; able to teach; and humility. The approaching of this researchs using quailitative and explorative method, of course to describe furtherly the meaning of tne word from linguistic side